Impact of SETD8/KMT5A overexpression on hepatocellular carcinoma progression and prognosis - Norihiko Suzaki; Shinya Hayami; Atsushi Miyamoto; Masashi Nakamura; Tomohiro Yoshimura; Kensuke Nakamura; Yoshinobu Shigekawa; Atsushi Shimizu; Yuji Kitahata; Akihiro Takeuchi; Hideki Motobayashi; Shigehiro Osada; et al. (PLoS ONE, 2026)
Background Hepatocellular carcinoma has poor prognosis due to its high recurrence rate, even after curative surgery. Epigenetic regulators are known to play a critical role in cancer progression, and the histone methyltransferase SETD8/KMT5A has been reported to be overexpressed in various malignancies. In this study, we aimed to elucidate the role of SETD8/KMT5A in hepatocellular carcinoma. Methods We investigated SETD8/KMT5A expression in 345 primary hepatocellular carcinoma resection specimens through immunohistochemical staining. For functional analyses, we conducted a loss-of-function study of SETD8/KMT5A using hepatocellular carcinoma cell lines, including in vitro assays for proliferation, cell cycle, invasion, and RNA sequencing with gene ontology analysis. Additionally, we performed xenograft experiments in mice and performed similar experiments using the SETD8/KMT5A inhibitor UNC0379. Results All cases were divided into either the SETD8 high-expression (n = 197) or low-expression (n = 148) groups. The high-expression group exhibited significantly poorer 5-year overall survival and 2- and 5-year disease-free survival compared with the low-expression group (both p < 0.001). Multivariate analysis indicated that high SETD8 expression was an independent poor prognosis factor in overall ( p = 0.0255) and disease-free ( p = 0.0051) survival. SETD8/KMT5A knockdown suppressed proliferation by inhibition of G1 to S phase transition ( p < 0.001). Gene ontology terms were related to cancer progression, including cell adhesion, MAPK-related signaling and chromatin remodeling. SETD8/KMT5A knockout using CRISPR/Cas9 inhibited tumor growth ( p < 0.01) in vivo . Conclusions SETD8/KMT5A overexpression was associated with poor prognosis and was an independent prognostic factor in hepatocellular carcinoma. In vitro and in vivo analysis, the inhibition of SETD8 could repress hepatocellular carcinoma progression through the regulation of cell activity and cell cycle transition.